GUIDELINES ON THE DIAGNOSIS AND MANAGEMENT OF X-LINKED HYPOPHOSPHATEMIA - (:unkn) unknown (ISTANBUL UNIV, FAC MEDICINE, PUBL OFF, 2020)
X-linked hypophosphatemia (XLH) is the most common cause of rickets related to inherited renal phosphate wasting. XLH is associated with lower limb deformities, pain, poor mineralization of the teeth, and disproportionate short stature in children as well as hyperparathyroidism, osteomalacia, enthesopathies, osteoarthritis, and pseudofractures in adults. The characteristics and severity of XLH vary between patients. Because of its rarity, the diagnosis and specific treatment of XLH are frequently delayed, which has a detrimental effect on patient outcomes. The diagnosis of XLH is based on signs of rickets and/or osteomalacia in association with hypophosphatemia and renal phosphate wasting in the absence of vitamin D or calcium deficiency. Whenever possible, the diagnosis should be confirmed by molecular genetic analysis or measurement of levels of fibroblast growth factor 23 (FGF23) before treatment. An evidence-based guideline was published for recommendation on the diagnosis, treatment, and follow-up of XLH by a multidisciplinary team organized by a metabolic bone disease expert. In this article, the current recommendations - based on the published guideline was summarized and adapted for our country.
Keywords: X-linked hypophosphatemia; XLH; rickets; hypophosphatemic rickets; PHEX; concensus; guidelines; treatment; conventional; burosumab; PARATHYROID-HORMONE; MUTATIONAL ANALYSIS; RANDOMIZED-TRIAL; VITAMIN-D; RICKETS; FGF23; PHEX; CALCITRIOL; PREVALENCE; EXPRESSION